Research Dissemination of Indonesian Institute of Sciences (LIPI) 2017-2020: : A Bibliometric Profile - Muntiah, Ayu; Dewi, Athanasia Octaviani Puspita (Record and Library Journal, 2023)
Background of the study: Dissemination of the research results of the Indonesian Institute of Sciences (LIPI) in 2017-2020 as measured by the distribution of publications. Purpose: This study aims to determine the bibliometric profile of research results documents owned by the Indonesian Institute of Sciences (LIPI) for 2017-2020 which have been disseminated. Method: The research method used is a quantitative bibliometric method with descriptive statistical analysis, and co-authorship analysis and co-occurrence analysis with VosViewer software. Findings: There are three groups of findings: document distribution, research collaboration, and research trends, it is known that: (1) research documents on Scopus excel in large number, wide scope of various publications, and description about publication status and types of document access; (2) research documents on DOAJ excel in the scope of Indonesian local publications; (3) LIPI's researcher with the most research results is Sumowodagdo S.; (4) LIPI's research collaboration is consistent with the University of Indonesia and the National University of Singapore; (5) LIPI's research trends are consistent in Indonesian studies with Indonesia as the keywords. Conclusion: The domination of the largest number of LIPI's research documents, collaboration, and keyword is found in research results indexed by the Scopus. Increased research can be done on a list of keywords that appear less frequently. Countries and institutions that have little collaboration also need attention and increase their collaboration. Countries and institutions with frequent collaboration also need to be maintained.